Morphological Awareness and Vocabulary Development Among Kindergarteners With Different Ability Levels. (January 2014) - Ramirez, Gloria; Walton, Patrick; Roberts, William
Our goal was to investigate the growth of vocabulary and morphological awareness over time in the context of an intervention for kindergartners with different ability levels in these skills. Participants in this exploratory study were 108 children from schools serving socioeconomically disadvantaged neighborhoods. Results indicated that children significantly improved their morphological awareness skills and vocabulary over a period of 4 months (η p 2 = .61 for morphological awareness andη p 2 = .53 for vocabulary), with the greatest gains made by children who were initially low on these measures. Morphological awareness and vocabulary skills were reciprocally related; each made a unique contribution to growth in the other. The results suggest that it may be beneficial to combine instruction in vocabulary and morphological awareness and that kindergarten teachers can successfully do so with guidance.